Cytotoxic and anthelmintic potential of crude saponins isolated from Achillea Wilhelmsii C. Koch and Teucrium Stocksianum boiss - Ali Niaz; Shah Syed; Shah Ismail; Ahmed Ghayour; Ghias Mehreen; Khan Imran (BMC, 2011)
Abstract Background Saponins isolated from plant sources have a number of traditional and industrial applications. Saponins have pharmacological effects like anti-inflammatory, molluscicidal, antimicrobial, antispasmodic, antidiabetic, anticancer, anticonvulsant, anthelmintic, antitussive and cytotoxic activities. The current work describes the anthelmintic and cytotoxic activities of crude saponins of Achillea Wilhelmsii and Teucrium Stocksianum as these plants are rich with saponins. Methods Brine shrimp cytotoxic activity of crude saponins was determined by Meyer et al. (1982) at test concentrations of 1000 μg/ml, 100 μg/ml, 10 μg/ml, 7.5 μg/ml, 5.0 μg/ml, 2.5 μg/ml and 1.25 μg/ml. Percentage mortality of test concentrations was determined. Similarly, in vitro anthelmintic activity was determined against roundworms, tapeworms and earthworms. Albendazole and piperazine citrate at concentration 10 mg/ml were used as standard anthelmintic drugs. Results Crude saponins of Achillea wilhelmsii (CSA) and Teucrium stocksianum (CST) had, respectively, cytotoxic activity with LC50 values 2.3 ± 0.16 and 5.23 ± 0. 34 μg/ml. For in vitro anthelmintic activity, time for paralysis and death of parasites (parasiticidal activity) was noted. At concentration 40 mg/ml, crude saponins of Achillea wilhelmsii are 1.96 and 2.12 times more potent than albendazole against Pheretima posthuma and Raillietina spiralis, respectively. Similarly, at concentration 40 mg/ml, crude saponins of Teucrium stocksianum (CST) has 1.89, 1.96 and 1.37 times more parasiticidal activity than albendazole against Pheretima posthuma, Raillietina spiralis and Ascardia galli, respectively. Conclusion Crude saponins of Achillea wilhelmsii and Teucrium stocksianum have cytotoxic and anthelmintic activity. The crude saponins may be excellent sources of cytotoxic and anthelmintic constituents that warrant its isolation and purification for new drug development.